2021
DOI: 10.1126/science.abf4359
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic asymmetric and stereodivergent oligonucleotide synthesis

Abstract: We report the catalytic stereocontrolled synthesis of dinucleotides. We have demonstrated, for the first time to our knowledge, that chiral phosphoric acid (CPA) catalysts control the formation of stereogenic phosphorous centers during phosphoramidite transfer. Unprecedented levels of diastereodivergence have also been demonstrated, enabling access to either phosphite diastereomer. Two different CPA scaffolds have proven to be essential for achieving stereodivergence: peptide-embedded phosphothreonine-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 69 publications
0
32
0
Order By: Relevance
“…The PS stereochemistry is not controlled in standard solid-phase synthesis, which results in the production of stochastic, 2 n diasteroisomeric mixtures, where n is the number of chiral phosphorus atoms in the ASO sequence. Recent synthetic developments [ 12 , 13 ] have facilitated the access to stereo-defined oligonucleotides and to their biological evaluation, but the emerging literature is not unanimous. In some reports stereodefined ASOs improved biological activity [ 14 ], but others are less encouraging [ 15 ].…”
Section: Innovative Developments In Nucleic Acid Therapeuticsmentioning
confidence: 99%
“…The PS stereochemistry is not controlled in standard solid-phase synthesis, which results in the production of stochastic, 2 n diasteroisomeric mixtures, where n is the number of chiral phosphorus atoms in the ASO sequence. Recent synthetic developments [ 12 , 13 ] have facilitated the access to stereo-defined oligonucleotides and to their biological evaluation, but the emerging literature is not unanimous. In some reports stereodefined ASOs improved biological activity [ 14 ], but others are less encouraging [ 15 ].…”
Section: Innovative Developments In Nucleic Acid Therapeuticsmentioning
confidence: 99%
“…Asymmetric catalysis, 1 which is famous as the most economic and efficient tactic for the production of enantiopure substrates, has triggered a research fever in chiral pharmaceuticals, 2,3 pesticides, 4-6 perfumes, 7 imaging materials 8 and other elds. 9,10 As one of the masterpieces, asymmetric hydrogenation 11 has achieved unprecedented successes in both the academic and industrial communities, and was hence awarded the rst Nobel Prize in chemistry of the 21 st century. To date, heterogeneous asymmetric hydrogenation based on metal nanoparticles (NPs) [12][13][14][15] is more promising for implementation in industrial applications than conventional homogeneous metal-chiral ligand complexes owing to its convenience in product separation, catalyst regeneration, and continuous ow operation.…”
Section: Introductionmentioning
confidence: 99%
“…Merck developed a chiral bisimidazole catalyzed synthesis of phosphoramidate prodrugs through the diastereoselective addition of nucleosides to chlorophosphoramidates, proceeding via a cooperative mechanism of covalent activation of P(V) and general-base activation of the alcohol nucleophile (23). An alternative approach was demonstrated by Miller and co-workers in the catalytic, stereodivergent synthesis of P-stereogenic oligonucleotides from phosphoramidites via chiral phosphoric acid catalysis (24). Finally, in work that appeared as this study was being completed, Dixon and co-workers reported a catalytic, enantioselective desymmetrization of diaryl phosphonate esters by substitution with orthosubstituted phenols (25).…”
Section: Introductionmentioning
confidence: 99%